ANALISIS PRODUK WISATA DI PANTAI PADANG - Rahmadani, Putri; Yuliana, Yuliana; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aimed to analyze the tourism products in Padang beach which is seen from the four elements of the tourist attraction, food and beverage services, souvenir services, amusement and recreational services. This type of research is descriptive qualitative. Data collection techniques by using the method of observation, interviews, and documentation. These results indicate that the tourism products in Padang not managed properly, results showed that the analysis of tourism products in Padang beach can be described from the indicators, are: 1) tourist attraction, in terms of beauty is good enough but not all neatly arranged only partially and the persistence of the garbage that littered the roadside, uniqueness in the beach of Padang are monuments IORA and maelo pukek that can be called with catching the fish and any culture values embodied in Padang beach but very minimal only theater in the cultural park 2) eating and drinking services, in terms of the price of lack of standardization of food prices, any menu variations, the cleanliness of the food is not very clean because of its location in a side street 3) services souvenirs unfound of locations that sell souvenirs coast of Padang. 4) amusement and recreational services, games duck water and dragon boat, but the water is dirty and there is rubbish strewn and entertainment arts festival held in the department of tourism and for children's games used to be in Muaro restless but now extinct, and there are games vw cycle but he rental price does not correspond with the facility, and other types of recreational sports but that is not well-organized.Keywords: Travel Products, Padang Beach